Research on the Characteristics of Wind， Temperature， and Humidity in the Lower Atmosphere at Zhongshan Station in Antarctica in Summer - Yang HUA; Hong WANG; Yubin LI; Qizhen SUN; Rui WANG; Zhiqiu GAO (Science Press, PR China, 2025)
This study examines observational data of the lower atmosphere during the summer seasons at the Antarctic Zhongshan Station from November 2018 to February 2019 and December 2019.It explores the profile characteristics and diurnal variations of meteorological elements， as well as inversions and jets at the station.The wind analysis reveals that the station experiences predominant winds from the east to northeast directions.Wind speeds increase sharply with altitude， peaking at approximately 1.2 kilometers in the morning and 0.8 kilometers in the afternoon， with lower speeds observed later in the day， possibly due to the development of downslope winds and enhanced turbulent mixing from thermal convection.Low-level jets are mostly concentrated in the speed range of 8~12 m·s-1 and at altitudes between 800~1600 m， with multiple layers of jets identified.Temperature observations show the presence of a superadiabatic layer near the surface， with potential temperature gradually rising above this layer up to 3000 m， indicating a stable atmospheric structure.Further analysis of inversion layers demonstrates significant diurnal variations， with thicker and closer-to-ground layers in the morning and thinner but more intense layers in the afternoon， influenced by solar radiation and turbulence intensity.Multiple inversion layers corresponding to multiple jets are also observed， highlighting the connection between inversions and wind shear induced by jets.Humidity analysis indicates a decrease in specific humidity with altitude， particularly pronounced below 250 m.Specific humidity levels are lower in the afternoon compared to the morning up to 250 m.The study of humidity stratification reveals that the heights of maximum gradient changes in specific humidity coincide with the heights of inversion layers and low-level jets.